(untitled) (Ciencias de la Ingeniería y Aplicadas, 2022)
The objective of the present research is to identify the socioeconomic conditions of the Artisans of La Victoria (Ecuador) by means of information survey, to know the structure of housing, access to basic services, health, education and working conditions of artisans. The methodology applied was descriptive with a mixed approach, not experimental, counting as population 60 members that make up the "Association of Artisans La Victoria", those who maintain their ancient techniques use mud for the elaboration of crafts that market them to the general public. The main results were that most of the floors of their homes are composed of cement or earth, the walls are brick or block and the roofs are tiled, they have most basic services, they have a primary education training, do not have health insurance, the income received is not representative against expenses and they work an average of 40 hours a week.